(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This study aimed to explore the perfectionism degree and its levels among teachers in Al Batinah South Governorate according to the variables of type of education, years of work, gender, and educational qualification. The study sample consisted of (302) teachers, comprising (129) male teachers and (173) female teachers. The researchers developed a perfectionism scale due to the absence of a specific Arabic scale to measure perfectionism among teachers. The results indicated a moderate level of perfectionism among teachers in Al Batinah South according to the perfectionism scale. The results also showed differences in the level of perfectionism among teachers in Al Batinah South attributed to years of experience in favor of the group with 10 years or more. However, the results did not show differences in the level of perfectionism among teachers in Al Batinah South Governorate attributed to variables of gender, type of education, and educational qualification.